Salivary carcinosarcoma: insight into multistep pathogenesis indicates uniform origin as sarcomatoid variant of carcinoma ex pleomorphic adenoma with frequent heterologous elements - Ihrler, Stephan; Stiefel, David; Jurmeister, Philipp; Sandison, Ann; Chaston, Nicola; Laco, Jan; Zidar, Nina; Brcic, Luka; Stöhr, Robert; Agaimy, Abbas (Histopathology, 2022)
Aims: The formal pathogenesis of salivary carcinosarcoma (SCS) remained unclear, both with respect to the hypothetical development from either preexisting pleomorphic adenoma (PA) or de novo and the clonal relationship between highly heterogeneous carcinomatous and sarcomatous components. Methods and results: We performed clinicopathological and molecular (targeted RNA sequencing) analyses on a large series of 16 cases and combined this with a comprehensive literature search (111 cases). Extensive sampling (average 11.6 blocks), combined with immunohistochemistry and molecular studies (PA-specific translocations including PLAG1 or HMGA2 proven in 6/16 cases), enabled the morphogenetic identification of PA in 15/16 cases (93.8%), by far surpassing a reported rate of 49.6%. Furthermore, we demonstrated a multistep (intraductal/intracapsular/extracapsular) adenoma-carcinoma-sarcoma-progression, based on two alternative histogenetic pathways (intraductal, 56.3%, versus myoepithelial pathway, 37.5%). Thereby, early intracapsular stages are identical to conventional carcinoma ex PA, while later extracapsular stages are dominated by secondary, frequently heterologous sarcomatous transformation with often large tumour size (>60 mm). Conclusion: Our findings strongly indicate that SCS (almost) always develops from PA, with a complex multistep adenoma-carcinoma-sarcoma-sequence, based on two alternative histogenetic pathways. The findings from this novel approach strongly suggest that SCS pathogenetically is a rare (3–6%), unique, and aggressive variant of carcinoma ex PA with secondary sarcomatous overgrowth. In analogy to changes of terminology in other organs, the term “sarcomatoid carcinoma ex PA with/without heterologous elements” might be more appropriate.
CRIS-Team Scopus Importer:2022-12-16
Keywords: carcinosarcoma; gene fusion; HMGA2; molecular testing; PLAG1; pleomorphic adenoma; salivary glands; true malignant mixed tumour